Proximate Composition, In vitro Antioxidant and Anti-inflammatory Properties of Adansonia digitata and Belanites aegyptiaca Seeds - Mercy Badu; Mary-Magdalene Pedavoah; Nathaniel O Boadi; Irene Y Dzaye (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2021)
This study evaluated the nutritional and medicinal properties of seeds from Adansonia digitata (BSF) and Balanite aegyptiaca (DDSF) plant. Proximate chemical composition, mineral elements composition, flavonoids, phenolics, antioxidant capacity, and anti-inflammatory properties were studied. Results obtained revealed that DDSF had the highest moisture, crude fat and crude protein content of 7.66 %, 42.80 %, 20.37 % respectively, whilst BSF gave the highest ash, crude fibre and carbohydrate content. Elemental analysis revealed BSF had the highest Mg content (313.65 mg/100g) and DDSF gave the highest Ca content (118.62 mg/100g). Additionally, DDSF gave the highest total phenolics (18.89 mg TAE/ 100 g), total flavonoids (8.80 mg QE/ 100 g) as well as the highest total antioxidant capacity of (19.62 mg AAE/ 100 g) dry of extract. Based on results obtained in this study, seeds obtained from the Adansonia digitata and Balanite aegyptiaca could be a potential source of functional food and antioxidant agents.